PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN BERDISKUSI SISWA KELAS IV - Anis Fita Yuliana; Tita Tanjung Sari; Ach. Puniman (FKIP Universitas Wiraraja, 2019)
Factors that can affect the learning outcomes of IVB graders include: 1) teachers still use traditional learning methods (lectures) where students only pay attention, listen, and record material so that students have difficulty in understanding the subject matter delivered by the teacher; 2) lack of teacher creativity in using varied learning models; 3) the teacher also lacks the opportunity for students to express their opinions so that it impacts on students' skills, especially in discussions. The purpose of this study was to determine the use of inquiry learning models in integrated thematic learning and to determine the effect of the use of inquiry learning models on students' discussion skills on integrated thematic learning in class IVB MIN 2 Sumenep. This study uses a quasi experimental design design with the form of nonequivalent control group design. The sample in this study consisted of two classes, namely class IVA and class IVB. Class IVA as many as 24 students as the control class and class IVB as many as 24 students as the experimental class. The treatment applied to the experimental class was the inquiry learning model. The syntax or steps of inquiry used in researchers are 1) presenting questions or problems; 2) make a hypothesis; 3) design an experiment; 4) conducting experiments to obtain information; 5) collecting and analyzing data; 6) make conclusions. The results showed that 1) The use of inquiry learning models in the experimental class was more effective than the direct learning model in the control class; 2) inquiry learning model influences students' discussion skills. This is evidenced by the results of the t-test 2 Free Samples (Independent Samples t-Test). Where in the t-test 2 Independent Samples t-Test in the